FORMATIVE ASSESSMENT LITERACY: BUILDING PRE-SERVICE TEACHERS' CAPACITY FOR REAL-TIME LEARNING DIAGNOSIS (Лучшие интеллектуальные исследования, 2025)
ABSTRACT. This research aimed to develop and evaluate an effective methodology for building pre-service teachers' formative assessment literacy and their capacity for real-time learning diagnosis. The study employed experimental-pedagogical methods, surveys, observations, testing, and statistical analysis. The experiment was conducted during the 2023-2024 academic year at Tashkent State Pedagogical University and Samarkand State University education faculties with 120 pre-service teachers participating. The developed four-stage methodology significantly enhanced pre-service teachers' formative assessment literacy. Experimental group participants demonstrated superior results compared to the control group across all indicators. Theoretical knowledge increased by 48%, practical skills by 62%, and overall assessment competency by 56%. The comprehensive approach-based methodology effectively serves to develop pre-service teachers' formative assessment literacy and can be widely applied to improve the quality of teacher education.